A mesoscopic damage model for the low-cycle fatigue of an extruded magnesium alloy. (June 2023) - Wang, Ziyi; Wu, Shengchuan; Lei, Yu; Li, Hang; Yu, Chao; Zhou, Kun; Feng, Xiqiao; Kang, Guozheng
Highlights: A novel mesoscopic damage model for the low-cycle fatigue of mg alloy is proposed. Two energy-type damage variables are defined to quantify TB and GB damages. The features of extension twinning and basal fiber texture are accounted for. Damage evolution behavior is well simulated using the damage evolution equation. The predicted crack initiation lives are all located within the twice error band. Abstract: This paper presents a novel mesoscopic damage model to characterize the low-cycle fatigue damage evolution of an extruded AZ31 magnesium (Mg) alloy, taking into account the effect of twinning. The damage caused by the slip bands (SBs)–twin boundaries (TBs) and SBs–grain boundaries (GBs) interactions is treated based on the Tanaka–Mura model and the Eshelby inclusion theory. Strain energy values at the TBs and GBs are defined as the TB and GB damage variables, respectively. Explicit formulae for the TB and GB damage evolution are derived from the characteristics of the { 10 1 ¯ 2 } extension twin and the basal texture. A fracture energy-based crack initiation criterion is established, and the proposed damage model is validated against the existing experimental results. The model demonstrates its ability to reproduce the damage evolution processes, and the predictions of the crack initiation life are within the twice error band.